2017
DOI: 10.1016/j.cognition.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Teasing apart coercion and surprisal: Evidence from eye-movements and ERPs

Abstract: Previous behavioral and electrophysiological studies have presented evidence suggesting that coercion expressions (e.g., began the book) are more difficult to process than control expressions like read the book. While this processing cost has been attributed to a specific coercion operation for recovering an event-sense of the complement (e.g., began reading the book), an alternative view based on the Surprisal Theory of language processing would attribute the cost to the relative unpredictability of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 50 publications
7
25
0
Order By: Relevance
“…This view seems largely consistent with a recent study controlling for surprisal between coercion and non-coercion conditions (e.g. 'John began/ bought the book') and observing no differences in N400s nor any other significant ERP differences [9]. These authors suggested, however, that the absence of ERP correlates should not be taken to indicate that coercion did not take place, royalsocietypublishing.org/journal/rstb Phil.…”
Section: (A) Coercionsupporting
confidence: 88%
See 1 more Smart Citation
“…This view seems largely consistent with a recent study controlling for surprisal between coercion and non-coercion conditions (e.g. 'John began/ bought the book') and observing no differences in N400s nor any other significant ERP differences [9]. These authors suggested, however, that the absence of ERP correlates should not be taken to indicate that coercion did not take place, royalsocietypublishing.org/journal/rstb Phil.…”
Section: (A) Coercionsupporting
confidence: 88%
“…Other researchers do view compositionality not as a method but as a factual claim, open to empirical testing [4]. For those who see compositionality as a factual claim, a possible empirical research programme (related to the question raised in the next paragraph) is to investigate whether the operations postulated to enable compositional analyses of natural language sentences are reflected in online measures of human language comprehension [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…complementizers or relativizers; Sikos et al 2017) or condensation (e.g. coercion; Delogu et al 2017) in lexico-grammatical contexts that are highly predictive. Such studies show that language users seem to be concerned about informativity and try to modulate the amount of information in transmission by their linguistic choices.…”
Section: Introductionmentioning
confidence: 99%
“…Another important implication of the presented perspective on surprisal involves its mapping to Event-Related Potentials (ERPs). In the electrophysiological domain, surprisal has often been linked to the N400 component (Delaney-Busch, Morgan, Lau, & Kuperberg, 2017;Delogu, Crocker, & Drenhaus, 2017;Frank et al, 2015), the amplitude of which is inversely related to the expectancy of a word; the less expected a word, the higher N400 amplitude (Kutas, Lindamood, & Hillyard, 1984). Although the N400 component was previously taken to be an index of integrative processing (i.e., the updating of an unfolding utterance representation), it has recently been linked to the process of lexical retrieval, which is facilitated by lexical and contextual priming; that is, N400 amplitude is reduced if word-associated conceptual knowledge is preactivated in memory (Brouwer, Fitz, & Hoeks, 2012;Kutas & Federmeier, 2000;Lau, Phillips, & Poeppel, 2008;van Berkum, 2009van Berkum, , 2012.…”
Section: Surprisal Indexes Change In Situation Modelsmentioning
confidence: 99%